Multicultural Łódź as a site of memory after 1945 – variability and diversity - Kucner, Monika (A mosaic city: The culture-oriented description, 2023)
In the 19th and 20th centuries, Łódź was a place where different cultures, religions, languages and nationalities met. The impetus for this multinational melting pot was the textile industry, which attracted settlers from different parts of Europe. Within a few decades, Łódź developed from a small city into a large metropolis with multiculturalism as its distinguishing feature. Łódź was a multicultural city until the end of the Second World War. As a result of ethnic segregation, a large part of the German and Jewish population left the city. They nurtured their memory of Łódź in the new socio-political conditions, outside Poland, often in dispersion, in small clusters often concentrated around hometown societies. The article describes how various nationality groups (Poles, Germans, Jews) remembered the multicultural city after 1945, based mainly on memories and newspaper articles. The author also draws attention to the fact that they functioned in a range of socio-political realities, which determined their memory of the multicultural city.